Debate analysis according to the speech acts theory - Babarasul Nori Rasul; Muhsin Ali Husein (QALAAI ZANIST JOURNAL, 2024)
People don’t just to express their intentions only produce speeches, but through these statements, but also perform actions through them, That’s there are many hidden meanings in the explicit meaning of each sentence (news, question, command, surprise). One of the pragmatic theories, presented by Austin in the 1960s, can be pragmatically analysis for different meanings. Return to the surroundings of the speech, language is not only used for news and questioning, but also for some other purposes to enter the subject. The analysis of the debate, according to the theory of the speeches, will have some good results, because both Debater, along with the statements they make, have many hidden purposes, can be examined in detail.